Changes of masticatory force affects condyle cartilage development and primary ciliary gene expression in mice - HU Ziyue; ZHANG Shuai; SUN Yao (Kouqiang hemian waike zazhi)
[Objective:] To explore the changes in condyle cartilage development and primary ciliary gene expression after changes in masticatory force. [Methods:] Three-week-old C57BL/6J male mice were divided into 3 groups, and they were fed with normal diet (ND) for 2 weeks, soft diet (SD) for 2 weeks, and fed with 1 week of soft diet than 1 week of re-normal diet (RND). After collecting the samples, safranin O-fast green staining, toluidine blue staining, Masson staining, alkaline phosphatase (ALP) staining, and collagen typeⅡ(COL2) immunofluorescence staining were performed to observe changes in the condylar cartilage and subchondral bone. Primary ciliary gene expression was detected by real-time quantitative polymerase chain reaction (RT-qPCR). [Results:] Compared with the ND group, the SD group has thinner condyle cartilage, less extracellular matrix, and subchondral bone structure has changed. The primary cilia gene expression (Ift88, Ift140, Ptch1, Smo, Gli1) was decreased. Compared with the SD group, the above changes recovered in the RND group. [Conclusion:] Changes of masticatory force during growth will affect the development of condyle cartilage and primary ciliary gene expression in mice.